ANALISIS TINGKAT KEPUASAN SISWA/I SMA/ SEDERAJAT TERHADAP SISTEM ONLINE LEARNING DI INDONESIA - Heruna Tanty; Briana Febriani; Fedora Tanuwijaya; Inas Safira (Jurnal Education and Development, 2022)
Abstract Customer satisfaction is the level of consumer feelings after comparing the customer expectation with the reality they have faced. This research is conducted using qualitative methods to observe the high school student's satisfaction and the importance of the online learning system in Indonesia since the COVID-19 outbreak. The purpose of this study was to determine the attributes of online learning for high school/equivalent levels using the Customer Satisfaction Index or CSI method, which consists of five dimensions: Tangibles, Reliability, Assurance, Empathy, and Access. Based on the Importance Performance Analysis results, it is concluded that the main priority attributes for improving their performance are those in quadrant A. Attributes in quadrant C are the second priority attributes to be improved. Attributes in quadrant B are essential and have met the students' satisfaction, so they become assets to be developed. Attributes with a high level of satisfaction but considered less important can be found in quadrant D. There are 143 questionnaire results with the outcome of the overall data that student satisfaction with online learning has reached 79%, which indicates that students are pretty satisfied.